Depth of sedation as an interventional target to reduce postoperative delirium: mortality and functional outcomes of the Strategy to Reduce the Incidence of Postoperative Delirium in Elderly Patients randomised clinical trial - Sieber, Frederick (Br J Anaesth, 2019)
BACKGROUND: The Strategy to Reduce the Incidence of Postoperative Delirium in the Elderly trial tested the hypothesis that limiting sedation during spinal anaesthesia decreases in-hospital postoperative delirium after hip fracture repair. This manuscript reports the secondary outcomes of this trial, including mortality and function. METHODS: Two hundred patients (≥65 yr) undergoing hip fracture repair with spinal anaesthesia were randomised to heavier [modified Observer's Assessment of Alertness/Sedation score (OAA/S) 0–2] or lighter (OAA/S 3–5) sedation, and were assessed for postoperative delirium. Secondary outcomes included mortality and return to pre-fracture ambulation level at 1 yr. Kaplan–Meier analysis, multivariable Cox proportional hazard model, and logistic regression were used to evaluate intervention effects on mortality and odds of ambulation return. RESULTS: One-year mortality was 14% in both groups (log rank P=0.96). Independent risk factors for 1-yr mortality included: Charlson comorbidity index [hazard ratio (HR)=1.23, 95% confidence interval (CI), 1.02–1.49; P=0.03], instrumental activities of daily living [HR=0.74, 95% CI, 0.60–0.91; P=0.005], BMI [HR=0.91, 95% CI 0.84–0.998; P=0.04], and delirium severity [HR=1.20, 95% CI, 1.03–1.41; P=0.02]. Ambulation returned to pre-fracture levels, worsened, or was not obtained in 64%, 30%, and 6% of 1 yr survivors, respectively. Lighter sedation did not improve odds of ambulation return at 1 yr [odds ratio (OR)=0.76, 95% CI, 0.24–2.4; P=0.63]. Independent risk factors for ambulation return included Charlson comorbidity index [OR=0.71, 95% CI, 0.53–0.97; P=0.03] and delirium [OR=0.32, 95% CI, 0.10–0.97; P=0.04]. CONCLUSIONS: This study found that in elderly patients having hip fracture surgery with spinal anaesthesia supplemented with propofol sedation, heavier intraoperative sedation was not associated with significant differences in mortality or return to pre-fracture ambulation up to 1 yr after surgery. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov NCT00590707.